2011
DOI: 10.1186/1472-698x-11-s3-s6
|View full text |Cite
|
Sign up to set email alerts
|

Can rights stop the wrongs? Exploring the connections between framings of sex workers’ rights and sexual and reproductive health

Abstract: BackgroundThere is growing interest in the ways in which legal and human rights issues related to sex work affect sex workers’ vulnerability to HIV and abuses including human trafficking and sexual exploitation. International agencies, such as UNAIDS, have called for decriminalisation of sex work because the delivery of sexual and reproductive health services is affected by criminalisation and social exclusion as experienced by sex workers. The paper reflects on the connections in various actors’ framings betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…These included interventions targeted at the health facility[8–10], community[10, 11], and policy[12] levels. Given this dearth of information, the primary topical gap is a lack of explicit focus on human rights interventions in SRH research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included interventions targeted at the health facility[8–10], community[10, 11], and policy[12] levels. Given this dearth of information, the primary topical gap is a lack of explicit focus on human rights interventions in SRH research.…”
Section: Resultsmentioning
confidence: 99%
“…One review focused on the negative impact of discriminatory laws around sex work, including their impact on voluntariness of medical care and access to health services; yet the review itself found limited data regarding the positive impact of changes in policies on SRH outcomes (e.g. how law influences sex workers ability to avoid STIs or to access SRH services as opposed to measuring levels of HIV infection)[12]. Another included some review of how changes in policies positively impact human rights related outcomes such as access to FP, participation of diverse stakeholders, or equity, nondiscrimination, and quality of SRH care.…”
Section: Resultsmentioning
confidence: 99%
“…Where legal and cultural contexts make it feasible, the provision of legal protections and HIV/STI surveillance and treatment for adult film actors in Los Angeles might be used as a model for the provision of such services to the broader population of MSW 64 . In Brazil, ‘male sex workers’ can report sex work as an official occupation facilitating access to social benefits and there is a history of government-sponsored anti-homophobia social marketing campaigns; however, recent government changes in Brazil may negate these advances in HIV prevention 65 . Thus, while governmental entities are crucial stakeholders, it is communities of MSW that need to be supported to be at the anchor of an effective response to their needs.…”
Section: Hiv Prevention Treatment and Care Approaches For Mswmentioning
confidence: 99%
“…They are most egregious in climates ofcriminalization.The United Nations High Commissioner on Human Rights and UNAIDS hasrecommended decriminalization to uphold sex workers’ human rights and health, 9 as have the United Nations Special Rapporteur on Health and Human Rights, 20 the UNAIDS Guidance Note on HIV and Sex Work, 5 the Global Commission on HIV and the Law, 11 and the United Nations Development Program. 10 Sex workers, national and international advocates, 13,15,105106 also call for decriminalization premised on the importance of sex workers’ health and safety as a means of promoting health and human rights.The Supreme Court of Canada recently struck down key provisions of the law governing sex work to improve sex workers’ rights to life, liberty and security.…”
Section: Evidence-based Reform: the Human Rights Framework For Changementioning
confidence: 99%